Islamic Republic of Mauritania : Fifth Review Under the three-Year Extended Credit Facility Arrangement, Requests for Modification of Performance Criteria and Extension of the Arrangement-Staff Report and Press Release. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2012)
Mauritania successfully weathered several exogenous shocks during 2011-12. Political upheaval in neighboring countries has not had detrimental economic effects so far, but political uncertainty remains high. Resilient growth and a continued buildup of external and fiscal buffers characterize better-than-expected macroeconomic developments. Ambitious structural reforms are vital for generating broad-based inclusive growth, promoting employment, and reducing poverty. The authorities will continue to improve transparency and economic statistics. Policy actions laid the foundation for a sound macroeconomic performance, although important challenges and vulnerabilities remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet